Analysis of Geospatial Production Factors on Rice Productivity at IP 200 in Muara Lawai Village Muara Enim Regency of South Sumatra - supli rahim; Dian Sulistyani; Asvic Helida (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2026)
This study aims to analyze the effects of production factors and spatial patterns on rice productivity under the CI 200 cropping system in Muara Lawai Village, Muara Enim Regency. The study is motivated by limited land availability, high cropping intensity, and variability in input management among farmers, resulting in heterogeneous productivity. A survey method involving 30 farmers was applied, followed by descriptive analysis, Cobb-Douglas regression, and GIS-based geospatial analysis. The results indicate that land area, rice variety, weed control, and fertilizer combination significantly affect rice productivity. The combination of NPK, urea, and liquid organic fertilizer (POC) is the most dominant factor (β = 0.300), followed by variety (0.220), weed control (0.180), and land area (0.280). The Adjusted R2 value of 0.686 indicates strong explanatory power. Geospatial analysis reveals spatial heterogeneity influenced by irrigation conditions, accessibility, and input distribution. The study concludes that productivity improvement under CI 200 depends on integrated and site-specific management of production factors rather than land expansion.